Analisis Dampak Pandemi Covid–19 Terhadap Rasio Profitabilitas, Likuiditas, Dan Aktivitas Perusahaan Subsektor Perdagangan Ritel Yang Terdaftar di Bursa Efek Indonesia Periode 2019 – 2020 - Muhammad Riza Kurniawan; Purnamawati Purnamawati (Management Department of Economics and Business Of Trunojoyo Madura University, 2022)
This study aims to determine the impact of the covid-19 pandemic on the profitability, liquidity, and activity ratios of retail trade sub-sector companies listed on the IDX for the period 2019-2020. This research data was obtained before and when the covid-19 pandemic occurred. The data was processed using the Wilcoxon test. The population in this study were 25 retail trade sub-sector companies. By using purposive sampling, the number of samples is determined to be 24 companies in the retail trade sub-sector. The results of this study indicate that there are significant differences in company profitability before and when the covid - 19 pandemic occurred. Meanwhile, in liquidity and activity, there were no significant differences before and during the covid - 19 pandemic.